2016
DOI: 10.1002/jmr.2562
|View full text |Cite
|
Sign up to set email alerts
|

Putative alternative functions of human stefin B (cystatin B): binding to amyloid‐beta, membranes, and copper

Abstract: We describe studies performed thus far on stefin B from the family of cystatins as a model protein for folding and amyloid fibril formation studies. We also briefly mention our studies on aggregation of some of the missense EPM1 mutants of stefin B in cells, which mimic additional pathological traits (gain in toxic function) in selected patients with EPM1 disease. We collected data on the reported interactors of stefin B and discuss several hypotheses of possible cytosolic alternative functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 85 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…Cystatin B (CSTB, stefin B) is an endogenous inhibitor of intracellular cysteine proteases (1,2). Previously, we reported that CSTB is a progression marker of human epithelial ovarian cancer (OC) (3), a disease ranked as the eight most common cancer worldwide in females (4) and gynecological cancer with the highest rate of mortality in the United States of America (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin B (CSTB, stefin B) is an endogenous inhibitor of intracellular cysteine proteases (1,2). Previously, we reported that CSTB is a progression marker of human epithelial ovarian cancer (OC) (3), a disease ranked as the eight most common cancer worldwide in females (4) and gynecological cancer with the highest rate of mortality in the United States of America (5).…”
Section: Introductionmentioning
confidence: 99%
“…After the Smad-complex translocates into the nucleus, it acts as a transcription factor to regulate the expression of a target gene (21). Smad-independent Transforming growth factor-β/miR-143-3p/cystatin B axis is a therapeutic target in human ovarian cancer WENCAI GUAN 1 , XINGXING WANG 1 , QUNBO LIN 1 , JINGUO ZHANG 1,2 , WEIMIN REN 1,2 and GUOXIONG XU 1,2 pathways, such as the MAPK and PI3K signaling pathways, can also be induced by TGF-β to initiate signal transduction and gene regulation (23). The Smad-dependent and -independent pathways have been demonstrated to contribute to the pathogenesis of OC (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several types of inhibitors that target amyloid aggregation are under development, including small molecule inhibitors, peptides, nanoparticles, antibodies, and proteins . Among them, peptides and peptidomimetics have been extensively studied for their specific interactions with Aβ .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to cystatin C, stefin B protects neurons from excessive oxidative stress [30,31] and protein misfolding [32]. Alternative functions, such as amateur chaperone function, have also been suggested from both experimental data and bioinformatic analysis [33]. A breakthrough in the understanding of the structure of cystatins and their mechanism of interaction with papain-like cysteine proteases, including lysosomal cathepsins, was provided by the three-dimensional (3D) structures of chicken cystatin monomer [34,35] and human stefin B-papain complex [36].…”
Section: Introductionmentioning
confidence: 99%